Antara Moralitas dan Realitas Politik: Sikap Komunikasi Islam Indonesia terhadap Krisis Palestina - Harahap, Juliadi Zurdani; Nasution, Hasyimsyah; Azhar, Anang Anas (Medan Resource Center, 2025)
This article examines how Islamic communication in Indonesia responds to the Palestinian crisis, highlighting the dynamic intersection of moral-religious values with domestic and international political realities. Using a literature review method, it analyzes key primary and secondary sources such as MUI fatwas, the communication strategies of Nahdlatul Ulama and Muhammadiyah, and the media's role in promoting Islam Wasathiyah (moderate Islam). The study finds that expressions of solidarity with Palestine are rooted not only in Islamic principles like ukhuwah Islamiyah and universal justice, but are also influenced by pragmatic political and diplomatic considerations. The novelty of this research lies in its exploration of how prophetic values are translated into strategic, moderate public communication amid global crises. It offers new insights into value-based Islamic messaging as a form of transnational humanitarian advocacy, revealing how moral consistency is sustained within Indonesia’s complex media and political landscape.